We will hold the line: o fandom como forma de participação dos fãs no desenvolvimento do universo transmidiático do jogo mass effect - Palomino, Paula Toledo (2015)
The advent and popularization of the Internet has enabled the cultural convergence movement, creating numerous online communities as well as the consolidation of collective intelligence. Without being blocked by geographical barriers that once separated them, fans of today are much more active, organized and eager for content. Their voices can now be heard by the companies holding the canonicity of the stories on the internet, through protests on social networks and unofficial content building (fandom culture). Their reactions can influence and even change the original plots. This work aimed to study this phenomenon from the fans perspective and their participation in the evolution of the transmedia universe of Mass Effect games (2007-2012), from Bioware, through its unofficial productions such as fanfiction, specific actions through crowdfunding platforms and interactions via social networking communities like Facebook, in response to the end of game trilogy, which generated great dissatisfaction due to an expectation not fulfilled (from the perspective of those fans). It analyzed the narrative complexity of the work, and how this aspect influenced the relationship with the fans, culminating in this highly organized protest action against the ending, forcing the company holding the canon content to retract and change the ending of its work.